PENYERAPAN LOGAM BERAT Pb DAN Cu MENGGUNAKAN KARBON AKTIF BERBASIS MAHKOTA NANAS DENGAN VARIASI KONSENTRASI KALIUM HIDROKSIDA - Meylia Susiana Dewi Putri; Awitdrus Awitdrus; Rita Kartini Manullang (Universitas Riau, 2020)
This study aims to determine the influence of concentration of potassium hydroxide (KOH) on the adsorption of Pb2+ and Cu2+ metal ions in industrial used water. The activated carbon was prepared from pineapple crown waste. Pineapple crown was pre-carbonized at 180oC for 1 hours. Chemical activation was done using KOH with variations in concentrations of 2, 3, and 4 M. The samples were irradiated by using a microwave at 630 Watt of output power for 15 minutes. KOH activation and microwave irradiation power were influenced to the physical properties of the samples. Activated carbon obtained were characterized using SEM, EDX, FTIR and AAS. The results showed that highest adsorption were obtained from activated carbon that was activated by KOH 2 M. Adsorption efficiency for Pb2+ and Cu2+ metals were 81.15% and 49.71%, respectively. The carbon chain structure shows the functional groups C-H, C≡C, O-H, C=C at wavenumber 2889.49 cm-1, 2360.97 cm-1, 2339.97 cm-1.